2019
DOI: 10.1029/2018jc014496
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Variations of Cross‐Shelf Nutrient Exchange in the East China Sea, as Estimated by Satellite Altimetry and In Situ Measurements

Abstract: Based on velocity and nutrient data from satellite and in situ measurements, we studied the temporal and spatial variations for 22‐year (1993–2014) cross‐shelf nutrient exchange at the 200‐m isobath section in the East China Sea. Since nitrate and phosphate concentrations were highly correlated (correlation coefficient of 0.95), only nitrate transport was investigated in detail. The cross‐shelf nutrient exchange is explored from whole to detail. The results show that the 22‐year averaged section‐integrated nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…A4). The model does not include an explicit compartment for nitrogen in the form of DON, although it can be included as in the work of Druon et al (2010), which adds semi-labile DOC and DON as state variables to the original Fennel et al (2006) model. They comment on the difficulties of validating the model with observations and highlight open questions even in the definition of both DOC and DON pools (see also Anderson et al, 2015).…”
Section: Biogeochemical Modelmentioning
confidence: 99%
“…A4). The model does not include an explicit compartment for nitrogen in the form of DON, although it can be included as in the work of Druon et al (2010), which adds semi-labile DOC and DON as state variables to the original Fennel et al (2006) model. They comment on the difficulties of validating the model with observations and highlight open questions even in the definition of both DOC and DON pools (see also Anderson et al, 2015).…”
Section: Biogeochemical Modelmentioning
confidence: 99%
“…The cross-shelf transport pattern in the ECS has also been wellvalidated by observational studies and numerical models (Ding et al, 2019;Zhang et al, 2019;Wang et al, 2021).…”
Section: B C Amentioning
confidence: 69%
“…On-shelf and off-shelf transport are crucial for marine processes, which have generated interest involving the geochemical budgets of biogenic elements (Ren et al, 2015;Ding et al, 2019;Zhang et al, 2021b). In this study, we examined the distribution and seasonal variations of dissolved Mn across the ECS from the eutrophic coastal waters to the oligotrophic KW.…”
mentioning
confidence: 99%
“…From 1987 to 2009, the nitrate flux was amplified by ∼12% in the PN section seen in Figure 1, meaning an upward trend of the transport of the Kuroshio waters (Guo et al, 2012). Ding et al (2019) calculated cross-shelf nutrient exchange, and suggested that the nitrate concentration (nitrate flux) at the 200-m isobath section in the ECS rose by up to 15% (25%) from 1993 to 2015. In the future, onshore intrusion is projected to increase (Hao et al, 2022;Seo et al, 2014), resulting in more nutrients being transported to the middle shelf of the ECS.…”
mentioning
confidence: 93%